Book Review (Res Medica, 2013)
CLINICAL CHEMISTRY IN PRACTICAL MEDICINE By C. P. Stewart and D. M. Dunlop.Fifth edition, 1958. E. & S. Livingstone Ltd., 27s 6d. To the casual observer, this new edition would seem to differ from its predecessors only in a somewhat more logical order, an additional 22 pages and an increase in price. Closer examination reveals, however, that a far more extensive revision has been undertaken,and that as many sections, notably the gastric and renal tests, have been reduced,the amount of new material included is greater than the additional pages might suggest. Large increases are to be found in those sections devoted to water andelectrolyte balance, to the steroid hormones, and to the metabolic abnormalities, while the accounts of such subjects as electrophoretic fractionation, the histamine stimulation of gastric function and the intravenous glucose tolerance curves are much expanded.